1992
DOI: 10.1002/tera.1420450303
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of developmental end points observed after 2,4,5‐trichlorophenoxyacetic acid exposure in mice

Abstract: A large-scale developmental toxicology study of 2,4,5-trichlorophenoxyacetic acid was conducted in four inbred strains and one outbred strain of mice. The most significant developmental effects observed were reduced fetal weight and increased incidences of cleft palate (malformation) and prenatal death (deaths/resorptions). The correlation coefficients among the proportion of deaths/resorptions, proportion of malformations, average fetal weights, and number of viable fetuses were investigated, with each variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…One approach (Catalano et al, 1993) considers the nonlive and live outcomes as being conditionally independent; hence, they can be modeled separately. However, the live outcomes are correlated (Ryan et al, 1991;Chen and Gaylor, 1992), so that " Indicates the number of animals that exhibit one or more malformations.…”
Section: Introductionmentioning
confidence: 99%
“…One approach (Catalano et al, 1993) considers the nonlive and live outcomes as being conditionally independent; hence, they can be modeled separately. However, the live outcomes are correlated (Ryan et al, 1991;Chen and Gaylor, 1992), so that " Indicates the number of animals that exhibit one or more malformations.…”
Section: Introductionmentioning
confidence: 99%
“…(1991) and Chen and Gaylor (1992) demonstrated a relationship between normal foetuses in rodents and foetal weight and suggested that some malformations may result from inadequate growth. Thus, the ratio N ( d , t ) / N ( O , t ) is used as a basis for a dose-response modelling of developmental effect.…”
Section: A Dose-response Model Based On Growthmentioning
confidence: 96%
“…Researchers exposed pregnant mice to different doses of the herbicide 2,4,5-trichlorophenoxyacetic acid (2,4,5-T) during gestation and recorded the number of implanted fetuses and the number of fetuses that died, were resorbed, or had a cleft palate (Holson and others, 1992;Chen and Gaylor, 1992). They observed the number of implanted fetuses, number of "affected" fetuses, and the dose of 2,4,5-T for each mouse in the experiment and are given in Table 1 of George and Bowman (1995).…”
Section: Developmental Toxicity Of An Herbicidementioning
confidence: 99%